Konsep dan Implementasi Merdeka Belajar pada Evaluasi Pembelajaran Pendidikan Agama Islam - Salman Hudri; Khotibul Umam (Moderasi : Journal of Islamic Studies, 2022)
This paper aims to determine the effect of the concept of merdeka belajar and its implications in the evaluation of Islamic Religious Education Learning. This paper uses a qualitative approach and literature study methods. Based on the results of the discussion, evaluation consists of measurement and assessment. In the context of learning, evaluation has a very important and strategic position, because it is included in the learning steps. The aim is to determine the effectiveness and efficiency of the learning system. The scope includes evaluation in learning programs, learning processes, and learning outcomes. In general, the evaluation principles consist of continuity, comprehensive, fair, objective, cooperative, and practical. Specifically, the principles consist of coherence, coherence, pedagogy, and accountability. Based on the literature review that has been carried out, the policy of the Ministry of Education and Culture, Nadiem Makarim, is known as the "merdeka belajar " policy. This policy includes 4 things: Ujian Sekolah Berstandar Nasional (USBN) developed by each school; the Ujian Nasional (UN) changed to a Asesmen Kompetensi Minimum (AKM) and a character survey; freedom of educators to Rencana Pelaksanaan Pembelajaran (RPP); and flexibility in Penerimaan Peserta Didik Baru (PPDB). Dalah Deka Learning aims to create students who are innovative, creative and based on community needs, the world of work, as well as a comprehensive assessment. As for in this article, the researcher concludes that: the development of evaluation is based on the purpose of human creation, which is to become a caliph on this earth. Thus, Islamic Religious Education educators must be able to evaluate the development of students covering aspects of Cognitive (aqliyah), Affective (qolbiyah), and Psychomotor (amāliyah).